IMPLEMENTASI KETERAMPILAN BELAJAR PESERTA DIDIK DALAM MENGEMBANGKAN SIKAP DAN KEBIASAAN BELAJAR YANG BAIK DI SMPN 2 PULAU PUNJUNG DHARMASRAYA - Maifitra, Maifitra; Kasih, Fitria; Nita, Rahma Wira (Bimbingan dan Konseling, 2013)
Presenting of problemâs research is to describe learning skill of students to improving good attitude and learning habit in SMPN 2 Pulau Punjung Dharmasraya. This research was done in SMPN 2 with total sampleÂ are 92 students. The instrument which Â is used is questionnaire the result of research found that generally learning skill of students is learning skill that mean (1) The reading skill is 63,04%. This category is good, (a) 42,39% is good in survey (b) 35,87% is good in question (c) 43,88% is good in read (d) 46,74% is good in recite (e) 35,87%Â is good in review (2) 64,13% is good category in implementation of assignment orientation (a) 59,78% is very good in schedule arrange (b) 63,04% is good in avoid theÂ things which disturb activities learning (c) 48,91% is good in asking auxiliaries (d) 36,96% is good in prepared the materials to make assignment (3) 67,39% is good in implementation to follow the examination (a) 67,39% is good to keep physical condition (b) 52,17% is good in calm attitude (c) 47,03% is good in self confidance (d) 56,52% is good in more understanding (e) 36,96% is good in focus thinking andÂ feeling (f) 44,57% is good enough in understanding all examinationÂ skill (g) 50,00% is good in be careful and accurate. From the description above can be concluded that implementation of learning skill of students improving good attitude and learning habit in SMPN 2 in order it can be defended and increased.Â Therefore the studentsâ more understanding about learning skill, improving skill and good learning hablt.